Use of a neuro-evacuation device for the endoscopic removal of third ventricle colloid cysts - Peron, Stefano; Galante, Nicola; Creatura, Donato; Sicuri, Giovanni Marco; Stefini, Roberto (Frontiers in Surgery, 2023)
Background: Colloid cysts are benign tumors usually located at the level of the foramen of Monro and account for approximately 1% of all intracranial tumors. Endoscopic surgical treatment represents the approach of choice for removal of these tumors and is usually preferred over transcortical or transcallosal microsurgical approaches.Our purpose is to demonstrate the feasibility of endoscopic removal of colloid cysts using a novel aspiration and fragmentation system, currently designed for evacuation of cerebral hematomas.We performed an evaluation of the results obtained in patients with symptomatic colloid cysts of the third ventricle operated on using an endoscopic neuroevacuation system